2013
DOI: 10.1149/05701.3023ecst
|View full text |Cite
|
Sign up to set email alerts
|

SOFC Long Term Operation in Pure Methane by Gradual Internal Reforming

Abstract: A solid oxide fuel cell was designed to be operated in pure methane, without reforming or carrier gas. The fuel cell was built up from conventional NiO-YSZ anode supported cell with a specific Pt screen-printed anodic collecting system and a Ir-CGO catalytic layer. The operation principle is based on Gradual Internal Reforming. After an initiation in H 2 for 30 minutes, the cell was operated for almost 2000 hours in pure and dry CH 4 with a fuel utilization rate of 30 %. Intrinsic gradual degradation of 15 %/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…After a mid‐term operation on cell 1 (∼2,000 h at 800 °C), careful SEM and EDX observations of the cathodic side of the fuel cell indicated that CM2 glass did not spread on the cells components during experiments at high temperature. These results were reported elsewhere 24.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…After a mid‐term operation on cell 1 (∼2,000 h at 800 °C), careful SEM and EDX observations of the cathodic side of the fuel cell indicated that CM2 glass did not spread on the cells components during experiments at high temperature. These results were reported elsewhere 24.…”
Section: Resultssupporting
confidence: 92%
“…The use of CM2 glass in complete fuel cells and the characterization of the systems confirmed that CM2 glass was adequate for SOFC applications at 800 °C. Indeed, the OCV of the cell 1 at 800 °C after few weeks at high temperature was unchanged 24. The decrease of the operating temperature at 760 °C reduces the power density of the cell by a factor 2.…”
Section: Discussionmentioning
confidence: 96%
“…The catalytic conversion of methane into hydrogen by steam reforming over Ir-CGO catalysts was previously investigated (18). Gradual internal reforming, was already demonstrated in electrolyte supported cells using pure and dry methane (7,8,(11)(12)(13)18) and ethanol (14)(15)(16) as the fuel. The catalytic aspects towards steam reforming were also intensively described (7,8,20).…”
Section: Resultsmentioning
confidence: 99%
“…Anode supported fuel cells were designed with the architecture described and studied in this paper . Specific anodic current collectors were developed to ensure a good current collection in between the Ni‐YSZ anode and the Ir‐CGO catalyst, with poor electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%